Validation of the Cycling Behavior Questionnaire: A tool for measuring cyclists' road behaviors (2018)
Introduction Even though cycling is an activity whose benefits in terms of urban mobility and health are globally recognized, its disproportional growth during the past few decades has led to some unexpected dynamics. In fact, the increasing number of traffic injuries and deaths involving cyclists has a high cost for public health systems. Considering the available empirical evidence, aberrant and positive behaviors on the road constitute relevant predictors for the injuries suffered by road users. Nevertheless, the scarcity of tools that measure and evaluate the behavior of road users, especially in the case of cyclists, constitutes a serious lack in terms of explaining, intervening and preventing traffic crashes through behavioral approaches. Objective This study had two essential purposes: first, to describe in detail the validation of measurement of risky and positive road user behaviors of cyclists using the Cycling Behavior Questionnaire. Second, to compare the mean scores of the validated version of the CBQ according to demographic and cycling-related factors. Method As a part of a larger collaborative research project, our data was collected from 1064 Spanish-speaking cyclists (between 17 and 80 years old) from 20 countries, who filled out an anonymous electronic survey on their riding behaviors. The data was analyzed using competitive Confirmatory Factor Analyses (CFA), thus obtaining basic psychometric values and an optimized structure for the scale. Results The obtained results suggest that the CBQ has a clear factorial structure, items with high factorial weight, and good internal consistency. In particular, the results of the latent variable model with three factors, which were labeled errors, violations and positive behaviors, show that the CBQ is satisfactorily adjusted. Conclusion The findings of this research support the idea that the CBQ may have important applications in the improvement of road safety through the study of cyclists' behavioral factors and their relationship to demographic and cycling-related factors.